In Store Display, Product Quality, And Price Discounts On Impulse Buying Decisions At Indah Bordir Sidoarjo Store - Rizki Dwi Rahmania; Lilik Indayani; Oetarjo Oetarjo (Publikasi Indonesia, 2023)
This study aims to identify and prove the effect of in-store displays, product quality and price discounts on impulse buying decisions at the Indah Embroidery store in Sidoarjo. The research was conducted using a quantitative approach, with a sample of 100 respondents, namely consumers at the Indah Embroidery shop who live in Sidoarjo with ages 18-45 years. Data collection was carried out using a questionnaire and analyzed with multiple linear regression analysis using the SPSS program. The results showed that in-store displays, product quality and price discounts proved to have a significant effect on impulsive buying at the Indah Embroidery shop in Sidoarjo.